LMA or vivipary? Wheat grain can germinate precociously during grain maturation under the cool conditions used to induce late maturity alpha-amylase (LMA) - Peery, Sarah R.; Carle, Scott W.; Wysock, Matthew; Pumphrey, Michael O.; Steber, Camille M. (Frontiers in Plant Science, 2023)
This study found that wheat (Triticum aestivum) grain can germinate prior during the maturation phase of grain development, a phenomenon called vivipary, and that this germination is associated with expression of the enzyme alpha-amylase. Farmers receive severe discounts for grain with low falling number (FN), an indicator that grain contains sufficiently elevated levels of the starch-digesting enzyme alpha-amylase to pose a risk to end-product quality. High grain alpha-amylase can result from preharvest sprouting/germination when mature wheat is rained on before harvest or from late maturity alpha-amylase (LMA) when grain experiences cool temperatures during the soft dough stage of grain maturation (Zadok stage 85). In an LMA-induction experiment, low FN was associated with premature germination or vivipary, presumably due to not only cool but humid growth chamber condition. This suggested that alpha-amylase expression might result from premature germination during LMA experiments or on a cool, rainy day in a farmer’s field. When a spring wheat panel with known LMA phenotypes was subjected to cool misting (18°C day/7.5°C night) during grain maturation (Zadok stages 83-87), 5 of the 6 LMA susceptible lines and one of the two LMA resistant lines showed visible sprouting on the mother plant. Thus, susceptibility to vivipary did not always correspond to LMA susceptibility. Moreover, when LMA-induction was performed with a dehumidifier, cool temperatures alone could induce LMA without visible sprouting suggesting that LMA can occur without vivipary. Vivipary was strongly induced during the soft to hard dough stages of grain maturation (Zadok stages 83-87) at the cooler incubation temperatures used for LMA-induction (18°C day/7.5°C night) as opposed to warmer conditions (25°C day/18°C night), suggesting that thermodormancy prevents germination during grain maturation. LMA and vivipary were induced by similar conditions resulting in similar levels of α-amylase expression, suggesting that they may have a similar impact on wheat quality.